PENGARUH SERTIFIKASI HALAL, MOSLEM BRAND AMBASSADOR SERTA BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK DENGAN TINGKAT RELIGIUSITAS KONSUMEN SEBAGAI VARIABEL MODERATING - Azmi, Shofi Arba'atu; Saifudin, Saifudin (Institut Agama Islam Negeri (IAIN) Ternate, 2023)
The purpose of this research is to determine the influence of Halal Certification, Muslim Brand Ambassador, Brand Image on Product Purchasing Decisions with the Level of Religiosity as a Moderating Variable. The data used in this research is primary data. This data was obtained from distributing questionnaires by researchers to respondents. The samples taken were 100 respondents. The data collection technique is random sampling. The data obtained was then processed using SPSS20 tools. This research uses a quantitative type of research using multiple linear regression analysis and Moderate Regression Analysis (MRA). The results of this research indicate that the halal certification variable does not have a positive and significant effect on purchasing decisions. The Muslim brand ambassador variable has no positive and insignificant effect on purchasing decisions. Then the brand image variable has a positive and significant effect on purchasing decisions. Furthermore, the level of religiosity variable is unable to moderate the influence of halal certification on purchasing decisions. The level of religiosity is unable to moderate the influence of Muslim brand ambassadors on purchasing decisions. And finally, the level of religiosity can moderate the influence of brand image on purchasing decisions.Keywords: Halal Certification; Muslim Brand Ambassador; Brand Image; Buying decision; Level of Religiosity